Dietary Inulin Supplementation Modulates Short-Chain Fatty Acid Levels and Cecum Microbiota Composition and Function in Chickens Infected With Salmonella - Song, Jiao; Li, Qinghe; Everaert, Nadia; Liu, Ranran; Zheng, Maiqing; Zhao, Guiping; Wen, Jie (Frontiers in Microbiology, 2020)
The current study investigated the effects of inulin on the gut microbiota, microbiome functions, and short-chain fatty acids (SCFAs) levels in speciﬁc pathogen-free (SPF) chickens infected with Salmonella Enteritidis (SE). SPF Arbor Acres chickens (n=240, 1-day-old) were divided into four groups: a control group (CON) fed a basal diet without inulin supplementation or SE infection, and three groups fed a basal diet supplemented with inulin 0%, 0.5%, and 1% (SE, 0.5%InSE, 1%InSE, respectively) up to 28-days-old, followed by SE challenge at 28 days of age. Cecal SCFA contents and microbiome composition and function were analyzed at 1-day post-infection. The results showed that SE infection significantly decreased cecal butyrate concentrations compared with the CON group (p < 0.05), while inulin supplementation reversed these changes compared with the SE group (p < 0.05). Inulin supplementation at 1% significantly increased the abundances of Lactobacillus and Streptococcus, and significantly decreased the abundances of Subdoligranulum and Sellimonas compared with the SE group (p < 0.05). The functional profiles of microbial communities based on metagenomic sequencing analysis showed that SE infection significantly increased the abundances of pathways related to carbohydrate metabolism, amino acid metabolism, energy metabolism, metabolism of cofactors and vitamins, and glycan biosynthesis and metabolism (p < 0.05), and signiﬁcantly decreased the abundances of pathways related to nucleotide metabolism, translation, and replication and repair compared with the CON group (p < 0.05), and these effects were reversed by inulin supplementation (0.5% and 1%) (p < 0.05). In conclusion, inulin modulated the dysbiosis induced by SE infection via affecting SCFA metabolism and microbial functional profiles.